2018
DOI: 10.1038/s41598-018-22589-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with prostate specific antigen testing in Australians: Analysis of the New South Wales 45 and Up Study

Abstract: Australia has one of the highest incidence rates of prostate cancer (PC) worldwide, due in part to widespread prostate specific antigen (PSA) testing. We aimed to identify factors associated with PSA testing in Australian men without a diagnosis of prostate cancer or prior prostate disease. Participants were men joining the 45 and Up Study in 2006–2009, aged ≥45 years at recruitment. Self-completed questionnaires were linked to cancer registrations, hospitalisations, health services data and deaths. Men with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 22 publications
3
18
0
Order By: Relevance
“…[40] While Australia has no organised screening program for prostate cancer, the prostate-specific antigen test (PSA) is widely used, especially by men of higher socio-economic position. [41] At least part of the apparently higher survival from prostate cancer in areas of less socio-economic disadvantage is due to overdiagnosis of indolent cancers by PSA testing. [42] Several studies have attempted to identify factors that mediate socio-economic inequalities in cancer survival, but the mediating effects of the identified factors are inconsistent within and between countries, mainly due to limitations of the data and applied methods and different health care systems.…”
Section: Discussionmentioning
confidence: 99%
“…[40] While Australia has no organised screening program for prostate cancer, the prostate-specific antigen test (PSA) is widely used, especially by men of higher socio-economic position. [41] At least part of the apparently higher survival from prostate cancer in areas of less socio-economic disadvantage is due to overdiagnosis of indolent cancers by PSA testing. [42] Several studies have attempted to identify factors that mediate socio-economic inequalities in cancer survival, but the mediating effects of the identified factors are inconsistent within and between countries, mainly due to limitations of the data and applied methods and different health care systems.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed dataset for 2005-2009 is unique, as it includes not only the number of tests, but also the number of men tested. 21 If coning was more common in less accessible or lower socio-economic areas, then the lower IRR estimates presented here for these areas might be spuriously low. This concept, called "episode coning," limits the cost of Medicare benefits paid for multiple pathology services in a single episode.…”
Section: Discussionmentioning
confidence: 74%
“…An analysis of the PSA testing participation in New South Wales (NSW) showed the highest PSA testing rates in men who had more frequent GP consultations. 21 If coning was more common in less accessible or lower socio-economic areas, then the lower IRR estimates presented here for these areas might be spuriously low.…”
Section: Discussionmentioning
confidence: 74%
“…15 Recent findings from the New South Wales 45 and Up Study reported PSA screening rates ranging from 41% in males aged 45-49 years through to 60% in those aged 60-69 years. 16 The close association in rise and fall of prostate cancer incidence and PSA testing suggests much of the changes in incidence relate to PSA screening rates. However, some clear deviations from this association between PSA testing and prostate cancer incidence beg explanation.…”
Section: Discussionmentioning
confidence: 99%